Optimizing Education Management Information Systems (EMIS) Implementation in Religious Education Institutions: Nvivo 12 Plus Analysis - Samiri, Muliani; Budianengsi, Citra; Nilwana, Andi; Nonci, Nurjannah (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research aims to analyze the implementation of the Education Management Information System (EMIS) in Religious Education Institutions of Sidenreng Rappang Regency. The research method used is qualitative with a descriptive approach. Research data was obtained through observation, interviews, and documentation. Data analysis techniques, including data reduction, presentation, and conclusion drawing, were carried out interactively. Data triangulation was used to ensure the validity of the findings. The data management process was carried out using Nvivo 12 Plus software. The results showed that the implementation of EMIS in religious education institutions in the Office of the Ministry of Religious Affairs of Sidenreng Rappang Regency. The findings show that in the communication aspect, there are obstacles in the dimension of message clarity that need to be optimized, causing uncertainty in implementation. In terms of resources, there are shortcomings in equipment and budgets that still need to support the smooth running of EMIS fully. However, aspects of disposition and government structure bureaucracy were running well, showing positive commitment and involvement from relevant parties. This research highlights the challenges and potentials of EMIS implementation within religious education institutions. Although there were constraints in communication and resources, positive dispositions and support from government structures helped to offset these challenges. The implication of the findings is the need to improve communication and optimize resource allocation to improve the effectiveness of EMIS implementation in the future.